2022
DOI: 10.1177/15589447221092055
|View full text |Cite
|
Sign up to set email alerts
|

Sauvé-Kapandji and Darrach Salvage Procedure Rates and Perioperative Parameters for Distal Radioulnar Joint Arthritis and Instability

Abstract: Background: Distal radioulnar joint (DRUJ) instability and arthritis are often painful and functionally limiting pathologies. Two common salvage procedures for DRUJ dysfunction are the Darrach and Sauvé-Kapandji (S-K) procedures. This study aims to provide an analysis of national Darrach and S-K procedure utilization rates and patient demographics. Methods: A national ambulatory surgery database, the 2018 Nationwide Ambulatory Surgery Sample, was filtered for Darrach and S-K procedure encounters. Data related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…77 A retrospective analysis involving 1,267 patients demonstrated that surgeons were more inclined to perform S-K surgery on younger and male patients. 78 Patients undergoing S-K surgery were 5 to 18 years younger than those undergoing Darrach surgery. [79][80][81][82] This preference might be attributed to the fact that S-K surgery preserves ulnar structures, maintaining ulnar stress transmission and considering grip strength improvements.…”
Section: Imaging Examinationmentioning
confidence: 99%
“…77 A retrospective analysis involving 1,267 patients demonstrated that surgeons were more inclined to perform S-K surgery on younger and male patients. 78 Patients undergoing S-K surgery were 5 to 18 years younger than those undergoing Darrach surgery. [79][80][81][82] This preference might be attributed to the fact that S-K surgery preserves ulnar structures, maintaining ulnar stress transmission and considering grip strength improvements.…”
Section: Imaging Examinationmentioning
confidence: 99%